2007
DOI: 10.1007/s11064-007-9299-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Mode of Cell Death in Substantia Nigra Following Intranigral Infusion of the Parkinsonian Neurotoxin, MPP+ in Sprague-Dawley Rats: Cellular, Molecular and Ultrastructural Evidences

Abstract: The potent parkinsonian neurotoxin 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) is known to cause dopaminergic neurodegeneration in nigrostriatal system. In the present study we investigated the nuclear morphology of cells in the substantia nigra pars compacta (SNpc) region of rats following unilateral intranigral infusion of the active metabolite, 1-methyl-4-phenyl pyridinium ion (MPP(+)), which resulted in a dose-dependent and prolonged dopamine depletion in the ipsilateral striatum. There appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Activated microglia not only bring damage to neurons through releasing a variety of noxious compounds [42,43] , but also recruit and activate more microglial cells, forming a vicious cycle that leads to more dopaminergic neuronal death. In the present study, after MPP + intoxication to SN, we observed a progressive TH-positive cell loss and behavioral defects in rats, which were consistent with previous studies [23,31,44] . Activation of microglia was seen from the third day after MPP + injection and lasted throughout our experiment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Activated microglia not only bring damage to neurons through releasing a variety of noxious compounds [42,43] , but also recruit and activate more microglial cells, forming a vicious cycle that leads to more dopaminergic neuronal death. In the present study, after MPP + intoxication to SN, we observed a progressive TH-positive cell loss and behavioral defects in rats, which were consistent with previous studies [23,31,44] . Activation of microglia was seen from the third day after MPP + injection and lasted throughout our experiment.…”
Section: Discussionsupporting
confidence: 93%
“…1C) Our results are broadly in accordance with previous study by Banerjee R et al who showed that intranigral MPP + infusion cause long-lasting damage to the nigrostriatal dopamine pathway, and did not show any sign of recovery in striatal dopamine content even after 90 d [31] .…”
Section: Intranigrally Injected Mpp + Induced Microglial Activation Asupporting
confidence: 92%
“…However, the apparent increase in the number of TH‐positive neurons in SNc could be an observational artifact, if we consider the distorted, shrunken perikarya of SNc TH‐positive neurons and the significantly increased number of small‐sized (30–50 μ m 2 ) and medium‐sized (50–80 μ m 2 ) neurons, but significantly decreased large (>80 μ m 2 ) neurons in the SN of MPTP and MPTP‐ plus melatonin‐treated group, as compared to the control. Therefore, it is a strong possibility that there is a general increase in the small‐sized neurons along the whole length of the SN, as MPTP treatment causes cerebral atrophy extending to the striatum, SN, and other parts of the brain and the increased number of TH‐positive neurons in the sections 18–30 could be resulting from the atrophy. In short, the present study features the unusual differential sensitivity of SNc dopaminergic neurons to MPTP treatment, which has not been heretofore reported.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, increasing doses of parkinsonian neurotoxins can cause a proportional reduction in striatal DA levels, thereby modeling PD with increased severity. 14,[16][17][18] There are several behavioral tests for animal models of PD that display the onset and progression of the disease. 19,20 Some of the well-established behavioral tests in unilaterally lesioned animal models of PD include amphetamine-or apomorphine-induced unilateral rotations, cylinder test, elevated body swing test, skilled-forelimb use test, beam balancing test, etc.…”
Section: Introductionmentioning
confidence: 99%